Evaluasi Kinerja Dump Truck di PT HPMU Kabupaten Ketapang - Sartika (Indonesian Society of Applied Science, 2022)
HPMU is a mining company and is located in Ketapang Regency, West Kalimantan Province. PT. HPMU has a production target of 360,000 tons/month. The realization of production sometimes does not reach the production target per month due to various factors including weather, availability of tools, use of tools, labor, and so on. This can be monitored in the mine control room, which is tasked with monitoring activities such as reporting ritase, ore mining, weighing, MGB hauling, reporting hours for repairs, reporting for fule filling, and reporting hours meter (HM). The monitoring results are used as a control and reference to analyze the level of production in the field so that if a problem occurs in production activities, it can be addressed immediately. This study aims to evaluate the performance using monitoring data from the mine control room. The calculation of the performance of the Hino type dump truck using data working hours, standby units, and repair hours. The performance evaluation of the means of transportation shows that dump truck (DT) with number 62 has the best performance among 5 dump truck units, with percentage values ​​of mechanical of availability (MA), physical of availability (PA), use of availability (UA) and effective of utilization (EU) 88%, 91%, 75% and 65% respectively. While the DT 65 has the worst performance among 5 dump truck units with MA, PA, UA and EU 59% values, respectively 72%, 77%, 76% and 59%.